Knowledge of dental trauma in a group of Chilean primary school teachers - Claudia Letelier; María Hernández (Universidad de Concepción., 2016)
Aim: To determine the knowledge and management of dentoalveolar trauma in primary school teachers in rural and urban schools in the district of Paillaco, Chile, in 2014. Methods: An observational study was conducted in 167 teachers in the city of Paillaco. A survey developed from the questionnaires proposed by McIntyre et al. and Yassen et al. was used. The survey, previously approved by 2 experts, was applied in person in the school facilities, after the application of a pilot test. Demographic characteristics of the participants and the frequency of correct responses by geographical location of the educational establishment (rural/urban) were analyzed. For the inferential analysis, the chi-square and t-tests (p<.05) were used. Results: 130 valid questionnaires (41.21±0.95 years, 68.4% women) were obtained. Participating teachers achieved an 83.3% of correct diagnosis of dentoalveolar trauma and a 55.5% of correct answers regarding its management. There were with no statistically significant differences in relation to geographical location. Conclusion: Primary school teachers in the district of Paillaco have a high level of knowledge of dentoalveolar trauma, but not of its management.